Comportamento de compra pró-ambiental: estudo com jovens consumidores - Radons, Daiane Lindner (2013)
From the perspective that natural resources are finite and that human behavior is affecting negatively the natural environment, a new attitude of society is perceived, that starts charge organizations act more responsible and committed to environmental issues. The effects of environmental concern by organizations go beyond compliance, studies show that consumers tend to reward actions of environmental responsibility of companies, once it passes to consider environmental issues at the time of consumption. From this perspective, recents researchs seek to identify the factors that affect the purchase decision of consumers, especially the green purchase behavior. Given the importance of environmental issues in consumption emerged the following question: "What factors influence the green buying behavior of consumers? To answer this question, a survey was conducted with the objective of check the green purchasing behavior of young consumers. To that end, was developed a research descriptive and causal, quantitative approach, and as instrument for data collection were administered questionnaires to university students, residents in Santa Maria / RS. The questionnaires were developed based on studies of Doughfous, Petrof and Pons (1999), that referred the innovative consumer behavior, and Lee (2008), which brought together eight scales, arising from previous research: i) green purchase behavior (LEE, 2008), ii ) environmental attitudes (KAISER, WOLFING; FUHRER, 1999), iii) environmental concern (SCHULTZ et al., 2004), iv) perceived seriousness of environmental problems (GARCIA-MIRA; REAL; ROMAY, 2005), v) perceived environmental responsibility (MANZO; EINSTEIN , 1987), vi) effectiveness perceived of environmental performance (MANZO; WEINSTEIN, 1987), vii) concern with self-image in the protection of the environment (LEE, 2007), viii) social influence (RYAN, 2001). With the exclusion of variables and inclusion of correlations, was obtained the final model, which includes eight constructs and twenty-seven variables. The fit indices proved satisfactory, being proven the validity and reliability of the constructs. The findings demonstrate that environmental concern, social influence, concern with self-image and innovative behavior positively affect the buying behavior green. It was also found the influence of generation and gender as moderators factors in the relationships investigated.